Integrated Transcriptome and Metabolome Analysis Revealed Mechanism Underlying Anthocyanin Biosynthesis During Flower Color Formation in Lagerstroemia indica - Zilong Gao; Zhuomei Chen; Jinfeng Wang; Weixin Liu (Horticulturae)
Lagerstroemia indica is a widely used ornamental woody plant known for its summer flowering and significant ornamental and economic value. While L. indica boasts a variety of rich flower colors, the molecular mechanisms underlying this color formation remain unclear. In this study, we selected three different flower colors of L. indica—white (W), red (R), and purple (P)—for transcriptome and metabolome analysis. The metabolome analysis identified 538 flavonoids, with 22 anthocyanins highly accumulated in the red and purple flowers. RNA-seq analysis annotated a total of 35,505 genes. Furthermore, we identified 42 differentially expressed genes (DEGs) involved in anthocyanin biosynthesis, with their expression levels aligning with anthocyanin content. Correlation analysis revealed that 19 MYB and 11 bHLH transcription factors are likely involved in anthocyanin biosynthesis. Additionally, we identified 59 auxin biosynthesis and signaling-related genes that are positively correlated with anthocyanin-related genes and metabolites, suggesting that auxin may play a role in regulating anthocyanin biosynthesis in L. indica. This study provides valuable insights into the regulatory mechanisms underlying anthocyanin accumulation and color formation in L. indica petals and identifies several potential genes, laying the groundwork for further research on regulatory mechanisms and genetic improvement of L. indica.